Kematangan Emosi Ditinjau dari Pola Asuh Otoriter Orang Tua pada Siswa SMP Talitakum Medan - Vidi Marsha Lorenza Silitonga; Fransiscus Josua; Rianda Elvinawanty (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This study aims to know the relationship between the authoritarian parenting with emotional maturity. The hypothesis in this study is there is a negative relationship between authoritarian parenting with emotional maturity, in assumption that the higher authoritarian parenting, then the higher emotional maturity and the lower authoritarian parenting, then the lower the emotional maturity itself. The subjects that used in this study are students at the SMP Talitakum Medan, in which the population consists of 98 students. Data obtained from the scale to measure authoritarian parenting and emotional maturity. The calculation of the data began by doing a test prerequisite analysis (the test of assumptions) that consists of a test of normality and a test of linearity. The data analysis in this study uses the Product Moment Correlation with SPSS 21 for Windows. The results of analysis showed the correlation coefficient at - 0,569 of the significance 0.000 (p < 0.05). This shows there is a negative relationship between authoritarian parenting with emotional maturity. The results of this study indicate that the variable of emotional maturity can be predicted by authoritarian parenting at 32.4 percent and 67.6 percent of the rest are influenced by other factors which not examined in this study. Based on the results of this study, the hypothesis is accepted that there is a negative relationship between authoritarian parenting with emotional maturity.